Charged Metallopolymers as Universal Precursors for Versatile Cobalt Materials1. Issue 50 (16th October 2013) - Zhang, Jiuyang; Yan, Yi; Chance, Michael W.; Chen, Jihua; Hayat, Jeffery; Ma, Shuguo; Tang, Chuanbing
<x xml:space="preserve">Abstract</x> A facile phase‐transfer ion‐exchange strategy was used to prepare cationic cobaltocenium‐containing polyelectrolytes with different counterions. These cobalt‐containing polymers were used to prepare cobalt‐based materials, including cobalt metal, cobalt phosphide, cobalt monoxide, cobalt–iron hybrids, and cobalt ferrite. Block copolymers and polymer brushes were also used to prepare cobalt‐based nanoparticles and nanowires.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>